2017
DOI: 10.1007/s00787-017-1060-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders and the risk for the subsequent first suicide attempt: results of a community study on adolescents and young adults

Abstract: Adolescents and young adults represent the high-risk group for first onset of both DSM-IV mental disorders and lifetime suicide attempt (SA). Yet few studies have evaluated the temporal association of prior mental disorders and subsequent first SA in a young community sample. We examined (a) such associations using a broad range of specific DSM-IV mental disorders, (b) the risk of experiencing the outcome due to prior comorbidity, and (c) the proportion of SAs that could be attributed to prior disorders. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 50 publications
(87 reference statements)
2
28
3
2
Order By: Relevance
“…The "presuicidal syndrome" described by Ringel in 1953 (18) refers to a possible suicidal decision chain and defines various components, including inhibited aggression turned against the self. Many young people in suicidal crises are ambivalent to the (28,29) -Non-suicidal self-injury (NSSI) (24,25) -Mobbing (26,27) -Mental illness: in particular, depressive disorder and bipolar disorders, acute psychotic disorder (especially with imperative acoustic hallucinations), post-traumatic stress disorder (23), dependency diseases, bulimia nervosa, attention deficit/hyperactivity disorder, anxiety disorders, disordered social behavior with elevated impulsiveness, personality disorders with elevated impulsiveness, delinquency (22,31,32) -Suicidal behavior in the family (25) and among friends (33) -Conflict, separation, or divorce of parents, loss of a parent, or a history of sexual abuse/maltreatment (24, 34) -Performance problems at school (35) -Chronic organic illness and physical disability (22) -Low socioeconomic status (36) last (19). Although their actions are intended to end their life, they are actually striving for another life (5).…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The "presuicidal syndrome" described by Ringel in 1953 (18) refers to a possible suicidal decision chain and defines various components, including inhibited aggression turned against the self. Many young people in suicidal crises are ambivalent to the (28,29) -Non-suicidal self-injury (NSSI) (24,25) -Mobbing (26,27) -Mental illness: in particular, depressive disorder and bipolar disorders, acute psychotic disorder (especially with imperative acoustic hallucinations), post-traumatic stress disorder (23), dependency diseases, bulimia nervosa, attention deficit/hyperactivity disorder, anxiety disorders, disordered social behavior with elevated impulsiveness, personality disorders with elevated impulsiveness, delinquency (22,31,32) -Suicidal behavior in the family (25) and among friends (33) -Conflict, separation, or divorce of parents, loss of a parent, or a history of sexual abuse/maltreatment (24, 34) -Performance problems at school (35) -Chronic organic illness and physical disability (22) -Low socioeconomic status (36) last (19). Although their actions are intended to end their life, they are actually striving for another life (5).…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…A German/Swiss study of adolescents and young adults showed that 93.4% of suicide attempts in this population were preceded by post-traumatic stress disorder. The authors concluded that these attempts at suicide might have been prevented by adequate treatment of the post-traumatic stress disorder (23). Young people with NSSI are more likely to have suicidal thoughts (OR = 2.95) (24) and to attempt to kill themselves (hazard ratio [HR] = 2.00) (25).…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…Sin embargo, además de la comorbilidad con los trastornos afectivos, también ha podido observarse la presencia de la ideación suicida en personas con agorafobia con otro tipo de variables, como el estrés postraumático, abuso de alcohol/fármacos/drogas, trastorno de personalidad límite o ruptura de parejas (Bados, 2006). En este sentido, en el trabajo de Miché et al (2017), la relación más estrecha fue entre suicidio y estrés postraumático, pero esa relación era mayor en la medida en que se incrementaba la comorbilidad (como la presencia de depresión y abuso de sustancias). En la citada investigación de Sareen et al, (2005), también encontraron una relación significativa entre agorafobia, trastorno de pánico e intentos de suicidio.…”
Section: Introductionunclassified
“…PTSD imposes a tremendous degree of suffering for families, decreases academic achievement for the child, and often carries the burden of additional mental illness such as anxiety disorders, depression, ADHD and substance use disorders (Herringa, ). Furthermore PTSD carries the highest risk of all mental illnesses among youth for first suicide attempt (Miché et al., ). Given that suicide is a leading cause of death in teens and young adults, the stakes could hardly be greater.…”
mentioning
confidence: 99%